The ethics of social research with children and families in Young Lives: practical experiences - Morrow, V (Palgrave Macmillan, 2012)
Research ethics exist to ensure that the principles of justice, respect, and the avoidance of harm are upheld, by using agreed standards. These principles are universal, though there many subtleties and diversities, and how principles are understood, interpreted, and practised can vary from place to place (Ulrich 2003). Following controversies involving deception and political involvement by researchers in the social sciences, ethical codes building on these principles were developed. These codes built on earlier ones developed for medical research on humans in the Nuremburg Code (1947, following the war crimes trials) and the Declaration of Helsinki (1964). The governance of research has expanded and now includes ethical practices in social research in general (ESRC 2005, 2010) and with children in particular (Alderson and Morrow 2011; Schenk and Williamson 2005). A burgeoning literature describes the processes, practices, and difficulties that occur in social research (see, for example, Armbruster and Laerke 2008; Iphofen 2009; Mertens and Ginsberg 2009; van den Hoonard 2002).